Behind the Wall: An Integrative Review of Defensiveness at Work - Yip, Jeffrey; Walker, Dayna O. H. (Academy of Management Annals, 2026)
Defensiveness is a pervasive challenge in organizational life. It emerges when leaders resist feedback, when teams deflect accountability, and when organizations develop routines that insulate them from change. Yet, research on defensiveness is fragmented, with four different perspectives that have developed in parallel: (1) psychodynamic research on defense mechanisms, (2) social cognitive studies on defensive reasoning, (3) behavioral research on observable defenses, and (4) organizational research on defensive routines and social defenses. In this integrative review of 523 peer-reviewed articles, we synthesize findings across the four perspectives to address the following questions: What is defensiveness? What triggers defensiveness? How does defensiveness unfold in organizations? What are effective ways to manage defensiveness? Across perspectives, we uncover a core paradox: defensiveness may offer short-term relief to individuals, but it creates dysfunction in the systems it aims to protect. Understanding this paradox is key to managing defensiveness and interrupting reinforcing defensive cycles in organizations.